Essential Oil from Pimenta pseudocaryophyllus (Myrtaceae) Leaves and Its Major Compounds Against the Mexican Bean Weevil - do Prado Ribeiro, Leandro; Donizeti Faria, Rodrigo [UNESP]; dos Santos Niculau, Edenilson; Luiz Padoan Gonçalves, Gabriel; Ansante, Thiago Felipe; das Graças Fernandes da Silva, Maria Fátima; Djair Vendramim, José (Springer Nature, 2023)
Eco-friendly strategies, including botanical insecticides, can contribute to stored products Integrated Pest Management (IPM) programs as alternatives to chemical insecticides. Thus, this study investigated the chemical composition and the fumigant insecticidal activity of the essential oil (EO) from Pimenta pseudocaryophyllus (Myrtaceae) leaves against adults of Mexican bean weevil, Zabrotes subfasciatus (Coleoptera: Chrysomelidae: Bruchinae), an important insect pest of stored beans in tropical conditions. In addition, the contribution of EO’s major compounds and binary mixtures on overall fumigant insecticidal activity against this pest was also assessed. Based in the GC-MS analysis, the phenylpropanoids chavibetol (39.60%) and methyl eugenol (9.10%) and the monoterpenoids 1,8-cineole (13.89%) and terpinolene (8.19%) were identified as major components. After 72 h of exposure, the EO showed promising insecticidal fumigant activity against Z. subfasciatus with a strong interaction effect of sex (LC50: 280.17 and 86.63 µL L−1 of air, respectively for females and males). When tested at their relative concentration in the crude EO, the phenylpropanoids chavibetol, methyl eugenol and the monoterpenoid 1,8-cineole as well as their binary mixtures caused the total mortality of exposed weevils, being equitoxic to a phosphine-based formulation used as a positive control. Thus, the EO from P. pseudocaryophyllus leaves is a promising fumigant insecticide to Z. subfasciatus management and its major compounds chavibetol, methyl eugenol and 1,8-cineole may be used to develop efficient and inexpensive artificial blends to IPM of stored beans.
Keywords: Allelochemicals; Monoterpenoids; Phenylpropanoids; Stored product IPM; Zabrotes subfasciatus